E-Module Development Assisted By a Professional Flip PDF Application on Virus Material - Nurfadila, Nurfadila; Hartono, Hartono; Muis, Abd (Biology Teaching and Learning, 2024)
This research aims to develop an e-module assisted by the Flip PDF Professional application on the topic of viruses, assess its validity, and assess its practicality. Adopting the development model by Borg & Gall, the study goes through seven stages: potential and problems, data collection, product planning, design validation, design revision, product testing, and product revision. Data were collected through questionnaires given to subject matter experts and media experts to test validity, as well as assessment responses from teachers and students to test the practicality of the e-module. The research findings indicate that the e-module has been developed for use as teaching materials and learning media in high schools. The product's validity from the assessment by subject matter experts is 95.67% and by media experts is 96.06% both categorized as "very valid". Assessment of the product's practicality also yields very positive results, with a percentage of teacher responses at 92.00% and student responses at 89.07%, both categorized as "very practical". This product is highly suitable for use as teaching materials and learning media for biology.Key words: e-module, flip pdf professional, teaching material, viruses